Spiritual distress in cancer patients: a synthesis of qualitative studies - Martins, Helga (2018)
Cancer affects individuals in all human dimensions. Cancer patients are more susceptible to spiritual distress. Several studies have addressed spiritual distress using quantitative designs; however, a qualitative approach to the experience of spiritual distress could provide a deeper understanding of the phenomenon. This study aims to synthesis the experience of spiritual distress as lived by cancer patients in qualitative primary studies. This is a literature review based on electronic databases search. A total of 4075 citations was identified and 23 studies were included. The most frequent qualitative research method was phenomenology (n = 15), and interviews were the main data collection method (n = 20). Two major themes have been identified related to the experience of spiritual distress: suffering and coping. Spiritual distress is an intimate, deep and suffering experience in life, which requires coping strategies and involves spiritual values and beliefs. Healthcare providers should be aware of this experience and recognize spiritual distress in cancer patients, as it is critical in providing holistic nursing care.